Readiness for Change in the State Civil Apparatus: A Systematic Literature Review - Ida Bagus Indra Narotama; Ni Nyoman Dian Sudewi (Syntax Idea)
Readiness for change in the State Civil Apparatus is a necessity in the midst of a world situation full of turmoil, uncertainty, complexity and ambiguity. This readiness also has a central role in achieving success in implementing development and bureaucratic reform. The current reality is that readiness for change in the State Civil Apparatus is still low. The State Civil Apparatus has not been fully able to adapt and implement the expected changes and is still stuck with old work patterns. The aim of this research is to analyze and explain the factors that influence readiness for change in the State Civil Apparatus. This research is a systematic literature review using PRISMA (Preferred Reporting Items for Systematic Literature Reviews and Meta-Analyses) guidelines. The sample from this research is secondary data obtained through searching journals in the Google Scholar and Semantic Scholar databases. The journals found were then selected using inclusion criteria and quality assessment, resulting in three research literatures. The research results show that there are three factors or components that can influence the readiness for change in the State Civil Apparatus, namely: perceived organizational support, work engagement and leader-member exchange